SUBSIDI PEMBELIAN MOTOR LISTRIK RODA DUA DALAM UPAYA MENINGKATKAN DAYA BELI MASYARAKAT - Astuti, Ismaya Indri (Universitas Diponegoro, 2024)
The Indonesian Government's commitment to entering the Industrial Revolution 4.0 era is demonstrated by the launch of the Making Indonesia 4.0 movement. Making Indonesia 4.0 has focused on five manufacturing sectors, including the food and beverage industry, textiles and clothing, chemicals, automotive and electronics. In the automotive and electronics sector, we strive to become the largest car manufacturer in ASEAN and develop the capabilities of the domestic electronics sector industry. As a form of effort to accelerate the formation of an electric vehicle ecosystem, the Government issued a policy regarding the expansion of recipients of the assistance program for purchasing two-wheeled electric motorbikes. This policy was marked by the issuance of Minister of Industry Regulation number 21 of 2023 concerning Amendments to Minister of Industry Regulation number 6 of 2023 concerning Guidelines for Providing Government Assistance for the Purchase of Two-Wheeled Battery-Based Electric Motorized Vehicles. This research uses a descriptive qualitative method, which will discuss providing subsidies for the purchase of two-wheeled electric motorbikes to increase people's purchasing power. This research is supported by literature data related to subsidies for electric motorbikes and sales of electric motorbikes, as well as various policy documents, regulations and legislation related to the provision of subsidies, as well as data related to the use of two-wheeled electric motorbikes in Indonesia. With the issuance of a policy from the Ministry of Industry, this research can answer the problem that we want to research, namely that providing subsidies can increase the selling value of electric motorbikes so that they can compete in the market.